Instrumen Asesmen Bagi Pendidik Dalam Proses Pembelajaran Biologi Berbasis Problem Based Learning: (Assessment Instruments for Teacher in Biology Learning Process by Problem Based Learning) - Meri Suriyani; Try Susanti; Darma Putra (BIODIK, 2020)
This study aims to produce PBL based assessment instruments (problem based learning) that are made to measure learning process for educators, in this case, the researcher will focus on the discussion about attitude. This research is an instrument development research adapted from ADDIE model, this model there are 5 stages: analysis, design, development, implementation and evaluation. Data collection and data analysis using different questionnaires and given to expert / expert teams and users of assessment instruments. To find out the feasibility of the instrument, the questionnaire was given to 3 expert teams / experts and got the score category 88%, then the score result on the assessment instrument is "Eligible" is used, instruments are also strengthened by small group and field trials. To find out the effectiveness and practicality of the disseminated instrument to several schools (implementation) of the instrument, the effectiveness questionnaire was given to 3 principals / users and obtained the score category 88%, then the scores result of the assessment instrument is "very Effective". In order to know the practicality of the instrument, the questionnaire of practicality was given to 3 principals / users and obtained the score category of 88%, then the scores result of the assessment instrument is "Very Practical". Abstrak. Penelitian ini bertujuan menghasilkan instrumen asesmen berbasis PBL (problem based learning) yang dibuat untuk mengukur proses pembelajaran bagi pendidik, dalam hal ini, peneliti akan memfokuskan pada pembahasan tentang sikap. Penelitian ini merupakan penelitian pengembangan instrumen yang diadaptasi dari model ADDIE, model ini terdapat 5 tahap yaitu: analysis, design, development, implementation dan evaluation. Pengumpulan data dan analisis data menggunakan angket yang berbeda dan diberikan kepada tim ahli/pakar dan pengguna instrumen asesmen. Untuk mengetahui kelayakan instrumen, angket diberikan ke 3 tim ahli/pakar dan didapatkan kategori skor 88%, maka hasil skor terhadap instrumen asesmen ini adalah â€œLayakâ€ digunakan, kelayakan instrumen diperkuat juga dengan adanya uji coba kelompok kecil dan lapangan. Untuk mengetahui keefektifan dan kepraktisan instrumen disebar kebeberapa sekolah (implementasi), angket efektifitas diberikan ke 3 kepala sekolah/pengguna dan didapatkan kategori skor 88%, maka hasil skor terhadap instrumen asesmen ini adalah â€œSangat Efektifâ€. Untuk mengetahui kepraktisan instrumen, angket praktikalitas diberikan ke 3 kepala sekolah/pengguna dan didapatkan kategori skor 88%, maka hasil skor tersebut diperoleh bahwa penilaian oleh kepala sekolah terhadap instrumen asesmen ini adalah â€œSangat Praktisâ€.